(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The objective of this study is to know the level of parents’ knowledge of autism disorder in Lattakia governorate, it aimed to find differences in the knowledge level of autism according to some variables :gender , place of residence, parents educational level, The sample consisted of 54 mother and father ,and a questionnaire was used to measure the knowledge level of autism disorder set up by the researcher. The results indicated that 74.1 % of the participants had a high level of knowledge , 25.9% had a medium level .The study did not show any notable difference regarding variables: gender , place of residence , but it shows a notable differences regarding parents educational level for the benefit of basic education.